KLean / Aznor Sarah Aqilah Azmadi ... [et al.] - Azmadi, Aznor Sarah Aqilah; Zulkifli, Effa Natasha; Samion, Syarafana; Othman, Nor’ain (Universiti Teknologi MARA, Kedah, 2019)
KLean, a cleanliness rating application which is designed to (1) assist authorities’ ability to respond by encouraging participation of tourists to rate touristic spots in Kuala Lumpur (2) propose a convenient and user friendly application for rating and (3) contribute to a greener and more sustainable environment for Kuala Lumpur will be the first application to allow tourists to give their perspective regarding the cleanliness level of selected sites. Since it is the first cleanliness rating application in Malaysia, KLean portrays a unique and fresh start towards cleanliness improvement in Kuala Lumpur as it allows ratings, comments and recommendations given by tourists to automatically connect with the destination’s authorities hence, prompt actions can be taken to improve any necessary conditions. Furthermore, not only is it convenient but it can provide various positive impacts as well towards the environment surrounding the tourist destination, the authorities in charge of the tourist destination and Malaysia’s image as a whole whereby more attention will be given towards the cleanliness of the destination in Kuala Lumpur, assist authorities in gaining perspective from tourists regarding the destination and improve Malaysia’s image as a whole. With the positive outcomes that KLean can bring, the chance of commercialization is present whereby with just an application, cost can be saved in terms of handling complaints where feedback forms printed can be changed into a more technology-friendly approach and clarifies only the significant improvements that need to be made towards a destination by ensuring that no unnecessary improvements are wasted.